Cost-Effectiveness of Antihypertensive Therapy in Ischemic Stroke Patients - Rowiyah Sufi Nurul Janah; F.X. Sulistiyanto Wibowo S; Yustisia Dian Advistasari (Dian Nuswantoro Semarang, 2026)
Ischemic stroke is an acute condition caused by the interruption of blood flow to the brain due to blood vessel obstruction, which can lead to permanent disability and death. Hypertension is a major risk factor and the most common comorbidity in ischemic stroke patients. The use of antihypertensive therapy in stroke patients plays a crucial role in controlling blood pressure and preventing complications, but it also increases the burden of medical costs. Therefore, a pharmacoeconomic evaluation is necessary to assess the cost-effectiveness of the therapy. This study aims to analyze patient characteristics and evaluate the cost-effectiveness of oral antihypertensive therapy in ischemic stroke patients at Hospital